(untitled) (Nonconventional Technologies Review, 2021)
In order to be able to adopt the best measures in any field, the main need is to know and differentiate between the different phrases and notions specific to the respective system. The purpose of this paper is to broaden the horizon of knowledge, to clarify the aspect considered non-compliant and to explain the correct form supported by examples of the notion of traffic capacity vs. infrastructure capacity and correlation with quality in the field of transport. In various specialized studies, in railway regulations and including in the laws of the European Union and national, only the idea of infrastructure capacity is incorporated, which is an inconsistent and erroneous expression. The actions of the quality management in the railway transport are included in both the strategic and the operative management, the particularity consists in the application of some measures of great technical and financial scope and with long durations of accomplishment. Therefore, the solutions to increase the quality of this service also consist in the ability to respond to new challenges, transport demand (allocation of traffic capacity) and limiting the effects of particularities in this sector.